Turning the poor rich: how the naming of middle class in Africa reshapes global perceptions of poverty and international development assistance processes - (:unkn) unknown (My University, 2013)
Panel Middle classes in Africa: the making of social category and its social meaning and uses mod. Dominique Darbon, Dieter Neubert (Université de Bayreuth) et Comi Toulabor
Keywords: African Research